Evaluation of Antioxidant Activity in Traditional Indonesian Herbal Medicine (Jamu) Using ABTS and DPPH Testing Methods - Rimbawan Apriyadi; Kartika Sari; Maulida Rachmawati; Muhammad Rafii Nur Fauzan; Miftakhur Rohmah (Universitas Ahmad Dahlan, 2025)
Herbal medicines are widely consumed as natural antioxidants to prevent oxidative stress-related diseases. Accurate assessment of antioxidant activity is essential, yet different methods may yield varying results. This study contributed to compare the antioxidant activities of ten commercial herbal medicines using ABTS (2,2’-azinobis- (3-ethylbenzothiazoline-6-sulfonic acid) and DPPH (2,2-diphenyl-1picrylhydrazyl) assays and evaluate the correlation between both methods. Ten herbal formulations were collected from local producers in Samarinda, Indonesia. Each product was mixed with low-fat milk (1:10 w/v) to enhance bio-accessibility and extracted via sonication and centrifugation. Antioxidant activity was analyzed using ABTS and DPPH radical scavenging assays. Percentage inhibition and IC₅₀ values were calculated. Statistical analysis was performed using GraphPad Prism 9.5.0 with Pearson correlation at a 95% confidence level. ABTS inhibition ranged from 10.54% to 72.73%, while DPPH ranged from 8.89% to 49.03%. IC₅₀ values were lower in ABTS (13.51–105.36 µg/mL) than in DPPH (20.11–165.50 µg/mL). A moderate positive correlation (r=0.5390) between inhibition results was observed but was not statistically significant (p=0.1079). Among all samples, the herbal formulation containing turmeric, betel leaf, areca nut, and manjakani exhibited the highest antioxidant activity with 72.73% inhibition (ABTS) and an IC₅₀ of 13.51 µg/mL. The differing sensitivities of ABTS and DPPH assays suggest that both methods should be used complementarily to obtain a comprehensive antioxidant profile of herbal products.